Palladium Nanoparticles Catalyzed Synthesis of Benzofurans by a Domino Approach - Mandali, Pavan Kumar; Chand, Dillip Kumar (Synthesis, 2015)
Palladium nanoparticles (PdNPs) were used as a catalyst for the one-pot synthesis of a variety of benzofurans by Sonogashira cross-coupling reactions under ambient conditions. The catalyst could be recycled without significant loss in its activity.
Keywords: palladium; nanostructures; catalysis; domino reaction; cross-coupling